Multimedia Security 1: Authentication and Data Hiding - Puech (Wiley Data and Cybersecurity, 2022)
Monograph
fulltext
Keywords: Communication, Networking and Broadcast Technologies; Components, Circuits, Devices and Systems; Computing and Processing